Analyzing Positive Politeness in Self-Introductions by Players on the Albion Online Forum - Muhammad Ziddan Akbar Assyari; Otong Setiawan Djauhari (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
Players often use online game forums to meet other players and to introduce themselves. This paper will examine the positive politeness strategies in self-introduction posts of the Albion Online forum. The qualitative descriptive design was applied, and fifteen posts were chosen purposely in the “Introduce Yourself!” category, with the data acquired from January to June 2025. This data was analyzed in Brown and Levinson's politeness theory by content-based pragmatic analysis. The results indicate that strategies of greeting, possessing enthusiasm, self-disclosure, joking, and inclusive language were used by the users to build relationships and decrease the social distance. These strategies indicate that users want to be accepted and aligned with the community. This research finds out that positive politeness is one of the necessary instruments of social interaction in digital gaming forums. This means that the online platforms have a major influence on communicative behavior. It is suggested that future research be conducted to add responses or interactions toward the investigation of the patterns of politeness in longer conversations.